Translation problems of English conversational vocabulary in the Thomas Hardy’s novel «Tess of the d’Urbervilles» (Eurasian Journal of Philology Science and Education, 2018)
The article discusses the features of conversational vocabulary translation in prose, as the same lexemes can have different stylistic signs in various academic dictionaries and clearly demarcated between mentioned ina speech lexemes. Analysis of English spoken language in the text of thenovel by Thomas Hardy’s «Tess of d’Erbervilley» in translation from Englishinto the Russian language shows that the translation of stylistically coloredvocabulary causes some difficulties because of its national specificity, semantical and emotional richness. In this regard, consideration of methodsof translation of spoken and stylistically reduced vocabulary from Englishinto the Russian language also remains topical. Sometimes translatorssolve relevant issues in the translation process. On the specific examplesis proved that the lexical and phraseological units of colloquial style ofany developed language reveals not only the specifics of the structural andgrammatical organization of the language, but, most importantly, reflectin their semantics process of history and culture of the people. They arefixed and transmitted from generation to generation, culture attitudes andstereotypes. It is also determined that the use of the local language maybe due to different geographical factors, as special colloquial phrases, dialects, and sometimes accents in the speech of the characters.